A new cross-linked enzyme aggregate biocatalyst for NAD+-booster production. Issue 23 (3rd March 2017) - Martínez-Moñino, Ana-Belén; Zapata-Pérez, Rubén; García-Saura, Antonio-Ginés; Cabanes, Juana; Sánchez-Ferrer, Álvaro
Abstract : Cross-linked enzyme aggregates of NMN deamidase were produced with enhanced stability and reusability to obtain nicotinic acid mononucleotide. Abstract : Nicotinamide adenine dinucleotide (NAD + ) is not only a redox cofactor/coenzyme but also a nutritional sensor molecule. Compounds that raise NAD + levels (NAD + -boosters) are used as dietary supplements, since they have shown great potential as calorie restriction mimetics to treat numerous age-related conditions. In this paper, an enzymatic bioprocess using recombinant NMN deamidase immobilized in the form as cross-linked enzyme aggregates (CLEAs) was developed to obtain one of the above compounds, nicotinic acid mononucleotide (NaMN). The immobilization process was optimized using different precipitants and dispersing technologies. CLEAs with full deamidase activity were recovered in short period by co-aggregation with albumin combined with a reciprocating dispersing methodology. These CLEAs showed high activity, storage and operational stability for the production of NaMN, suggesting the first time that CLEA technology could be used to obtain highly valuable NAD + -boosters. This is also the first report on a Ser/Lys catalytic dyad enzyme immobilized as CLEAs.